The Synergistic Effect Accelerates the Oxygen Reduction/Evolution Reaction in a Zn-Air Battery - Zhang, Yidan; Guo, Youmin; Liu, Tao; Feng, Fuxu; Wang, Chunchang; Hu, Haibo; Wu, Mingzai; Ni, Meng; Shao, Zongping (Frontiers in Chemistry, 2019)
Perovskite oxides are promising electrocatalysts towards oxygen reduction reaction (ORR) and oxygen evolution reaction (OER) due to their abundance and high intrinsic catalytic activity. Here we introduce Ag into Sm0.5Sr0.5CoO3-δ (SSC) to form a Ag-SSC catalyst by ultrasonication and apply it as the air electrode for a Zn-air battery. It finds that the introduction of Ag into SSC can transform the Ag-SSC into a good bifunctional electrocatalyst towards ORR as well as OER. For instance, a more active half-wave potential with a value of 0.76 V for ORR is obtained at 1600 rpm, while the OER overpotential is 0.43V at I=10 mA cm-2. Further characterization demonstrates that the improved catalyst activity of the Ag-SSC can be assigned to the synergistic effect generated between the Ag and SSC phases. The Zn-air battery with the Ag-SSC as an electrode not only gives a same discharge-charge voltage gap (1.33 V) with that of commercial Pt/C (1.33 V) but also presents an equivalent current efficiency (45.7% for Ag-SSC and 45.3% for Pt/C) at 10 mA cm-2. Moreover, the stability for 110 cycles is better. This result indicates that the Ag-SSC catalyst shows promise for use as a bifunctional electrocatalyst towards OER and ORR.